Application of Consecutively Assembled Boulders Around Hydraulic Structures (Journal of Environmental Science Studies, 2025)
The riverbed protection below hydraulic structures must require from the viewpoint of preservation of river environment. In the case of bridge pier, a deflected flow due to impingement to the front of pier makes water surface slope and undulation flows with stable and irregular form downstream of the pier. It is important to pay attention to the effects of irregular undulating flows on riverbeds, as even if the average flow velocity near the bottom is low, their ability to promote irregular transport of sand and gravel is not negligible. For the movable weir, if the river is wide, there will be multiple gates, and the flow deflected by impinging the gate pier with the support will form a flow like that of the bridge pier, and the undulations with stable wave and irregular wave will cause riverbed erosion over a long period of time. For the energy dissipator downstream of the low drop structures, jump formation is useful, but a concave curvature at the toe of the jump does not neglect, and the mainstream is located near the bed. The riverbed protection needs downstream of jump region. Recently, the author discovered that the installation of consecutively assembled boulders is effective in reducing the flow velocity near the bottom, and in controlling the mainstream during normal and flood stages. The ramp with the consecutively assembled boulders was constructed according to the author's proposal, the upstream and downstream migration for muti-aquatic animals in normal stages was confirmed in prototype. In this paper, to prevent local scouring occurring at the downstream of movable weirs, low-drop structures, check dams, and around bridge piers, the author experimentally demonstrated a riverbed protection method using seepage flow by placing crushed stone downstream of consecutively assembled boulders arranged in a parabolic shape. The experimental results revealed that the combination of assembled boulders installation and protection region with crushed stones makes effective application of the formation of seepage flow and supporting by the velocity field near the bottom. Further, the application of the consecutively assembled boulders in prototype was introduced, and the proposed structure might help ecological approach.